Primary cutaneous mucormycosis in an immunocompetent patient: a case report - Paudel, Deepak; Dahal, Raunak; Khadka, Dhan Kesar; Agrawal, Yamuna (Journal of Chitwan Medical College, 2021)
Mucormycosis is an infrequently encountered locally invasive, aggressive fungal infection that frequently occurs in patients with an underlying immunodeficiency. It is usually diagnosed on histopathology and treated with systemic antifungals. We report a case of 16 years old female who presented with swelling on the dorsum of nose with overlying redness and tenderness. As she did not respond to antibiotics and conventional treatment, computed tomography scan and fine needle aspiration cytology were performed which revealed an inflammatory lesion. However, her histopathological examination was a surprise for all of us as it came out to be mucormycosis. She was then started on oral antifungal, and responded well. Although a rare entity, primary cutaneous mucormycosis should always be kept in mind while evaluating any swelling if it doesn’t improve on conventional treatments and dealt accordingly.